Validation of the Italian version of the full and abbreviated Trust in Oncologist Scale. (5th October 2020) - Bani, Marco; Rossi, Emanuela; Cortinovis, Diego; Russo, Selena; Gallina, Francesca; Hillen, Marij A.; Canova, Stefania; Cicchiello, Federica; Longarini, Raffaella; Cazzaniga, Marina Elena; Bidoli, Paolo; Valsecchi, Maria Grazia; et al.
Abstract: Introduction: The Trust in Oncologist Scale (TiOS) is an 18‐item questionnaire aimed to assess the cancer patients' trust in their oncologist and has been validated in Dutch and English language. This study aims to validate the Italian version of the TiOS (IT‐TiOS) and the TiOS‐Short Form (IT‐TiOS‐SF). Methods: The IT‐TiOS was administered to 194 patients recruited in an Italian oncology department from April to December 2018. Data collected included socio‐demographic data, health and clinical information, satisfaction with the most recent oncology visit and trust in the regional healthcare system. Internal consistency, test–retest reliability, convergent and the structural validity of both the full and short form were tested. Results: Factor analyses indicated that neither four‐factor nor one‐factor models of the full scale were acceptable. However, confirmatory factor analysis supported the one‐dimensionality of the IT‐TiOS‐SF, and internal consistency assessed with Cronbach's alpha was 0.88. Mean scores on the IT‐TiOS‐SF correlated with satisfaction with the oncologist (rs = 0.64) and willingness to recommend the oncologist to others (rs = 0.67), confirming good construct validity. Conclusion: The IT‐TiOS‐SF demonstrates good psychometric properties and can be used to assess trust for both clinical and research purposes.